Le cellule staminali mesenchimali nel trattamento delle lesioni muscolo-tendinee - Scotto di Luzio, A.; Di Franco, S.; Peluso, F.; Riccardi, D.; D’Amato, A.P. (Lo Scalpello - Journal, 2019)
MESENCHYMAL STEM CELLS IN THE TREATMENT OF MUSCLE-TENDON INJURIES Tendon injuries are a cause of physical disability, especially in athletes. The challenge for orthopaedic surgeons is owed to the fact that injured tendons respond poorly to conventional treatments and stem-cell-based therapies may offer great potential to promote tendon regeneration tanks toh their proliferative, synthetic, and immunomodulatory activities. This work was aimed at providing an update on the current role and future directions of stem-cell-based therapies, discussing clinical cases. In spite of positive outcomes, additional clinical trials are needed to confirm the safety and efficacy of the treatment.